Ensaios sobre avaliação do programa farmácia popular do Brasil: equidade e sobrevivência empresarial - Silva, Maria Eduarda de Lima e (2018)
The present dissertation is composed by two essays that evaluate the Programa Farmácia Popular do Brasil (PFPB – Brazilian Popular Pharmacy Program), intended for the pharmacological treatment of Chronic Non-Communicable Diseases (CNCD) of high prevalence among Brazilian population, such as hypertension and diabetes. The first essay examines the regional allocation of resources from the PFP Band the Componente Básico da Assitência Farmacêutica (CBAF–Basic Component of Pharmaceutical Assistance), considering the relative availability of the program and the region potential needs. The approach used was Multiple Data Envelopment Analysis and data from the National Health Survey, the administrative and financial basis of the Program and the Support Room for Strategic Management of the Ministry of Health. The results demonstrate a regional inequality of access to medicines in the country, since the regions with the highest PFPB coverage are the richest localities. The comparison between the distribution of resources destined to the Program and the CBAF evidences the PFPB prioritization to the conventional pharmaceutical assistance in detriment of Sistema Único de Saúde (SUS – Health Unic System). Otherwise, the second essay evaluates the effect of the Aqui Tem Farmácia Popular program on the probability of business survival of pharmacies and drugstores. Therefore, we use data from 2004 to 2014 of all formal establishments in the sector and approach to survival analysis using the Cox proportional hazards model. The results shows a positive association between the increase in survival of pharmaceutical establishments and participation in the Program. As a result, on average, adherence to the Program reduces by 53.3% the death risk of pharmacies, in the way that the small establishments are the most benefited. Furthermore, the estimation of the survival rate by region demonstrates the stability of the found effects. This results shows the sustainability of AF strategy assumed by the Federal Goverment and these results can be use as an incentive to the participation of the North and Northwest establishments (in areas with minor PFPB participation).